2023
DOI: 10.3390/ijms241914491
|View full text |Cite
|
Sign up to set email alerts
|

(+)-Lipoic Acid Reduces Lipotoxicity and Regulates Mitochondrial Homeostasis and Energy Balance in an In Vitro Model of Liver Steatosis

Lucia Longhitano,
Alfio Distefano,
Angela Maria Amorini
et al.

Abstract: Non-alcoholic fatty liver disease (NAFLD) is characterized by the accumulation of lipids within hepatocytes, which compromises liver functionality following mitochondrial dysfunction and increased production of reactive oxygen species (ROS). Lipoic acid is one of the prosthetic groups of the pyruvate dehydrogenase complex also known for its ability to confer protection from oxidative damage because of its antioxidant properties. In this study, we aimed to investigate the effects of lipoic acid on lipotoxicity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 39 publications
1
2
0
Order By: Relevance
“…On the other hand, herein, the FFA-treated HepG2 cells exhibited a decreased mitochondrial respiration, increased ROS production [2 mM OA/PA (1/1)], mitochondrial fragmentation and TAG accumulation, with no change in MMP and cell death. The findings demonstrating a decreased mitochondrial respiration in FFA-treated HepG2 cells are in accordance with those of previous studies, although the findings regarding lipotoxicity are inconsistent ( 15 , 16 , 45 , 48 ).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…On the other hand, herein, the FFA-treated HepG2 cells exhibited a decreased mitochondrial respiration, increased ROS production [2 mM OA/PA (1/1)], mitochondrial fragmentation and TAG accumulation, with no change in MMP and cell death. The findings demonstrating a decreased mitochondrial respiration in FFA-treated HepG2 cells are in accordance with those of previous studies, although the findings regarding lipotoxicity are inconsistent ( 15 , 16 , 45 , 48 ).…”
Section: Discussionsupporting
confidence: 91%
“…On the other hand, it was surprising to observe that a significant decline in mitochondrial respiration in FFA-treated HepG2 cells did not result in more severe mitochondria damage and decreased cell viability. It is possible that the methods used to evaluate cell death in the present study may not have been as sensitive as those used in previous studies ( 45 , 48 ). Of note, the study by Doczi et al ( 63 ) demonstrated that the viability of HepG2 cells was not decreased by the complete inhibition of mitochondrial respiration.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation